Influence of weed species and density on lima bean yield and other pests - Sankula, Sujatha; Everts, Kathryne L.; Whalen, Joanne M.; VanGessel, Mark J. (Frontiers in Agronomy, 2024)
Weeds interfere with lima bean production by reducing crop yield, hindering harvest, and contributing contaminants to harvested beans, yet there are very few trials documenting the impact of weeds on lima bean. This research was designed to evaluate weeds on lima bean yield, quality, as well as Rhizoctonia solani and pod-feeding insects in order to assist in implementing a more integrated approach to pest management. Field studies at four sites evaluated the impact of common cocklebur (Xanthium strumarium L.), jimsonweed (Datura stramonium L.), and ivyleaf morningglory [Ipomoea hederacea (L.) Jacq.] at densities of 0, 7, 10, or 20 plants 10 m-1 row in the presence and absence of Rhizoctonia solani on lima bean (Phaseolus lunatus L.). The planting dates of late June to mid-July represented a typical planting period for the mid-Atlantic region of USA, while one site represented an early planting date in this region (28 May). Differences in response to weed competition for total lima bean yield, marketable yield, yield components, and R. solani discoloration on lima bean occurred at one or more sites. Weed competition from 7 plants 10 m-1 of row or higher, reduced number lima bean pods by as much as 40%. However, weed density had little impact on percentage of flat, plump, or dry pods. Marketable yield was reduced at two sites in response to 7 plants 10-1 row (19% yield loss) and higher weed densities resulted in 29 to 33% yield loss. The presence of lima bean resulted in 40 to 60% reduction of common cocklebur and jimsonweed biomass and burs or seeds compared to weeds grown without crop competition. Weed competition in lima bean was influenced by many factors including weed species and planting date. Weed management is important to not only preserve yield but limit weed seed return to the soil seedbank and maintain harvest efficiency.